Urban Densification: An Effective Sustainability Solution Against Urban Sprawl - Aïcha Chetara; Leila Djaghrouri; Djamila Djaghrouri; Moussadek Benabbas (Prostor, 2025)
City densification is typically presented as a strategy to address the challenges of urban sprawl and rapid soil degradation. The aim of this article is to analyze the morphology of the city of Batna, Algeria, using remote sensing and GIS. This approach is part of the prevailing concern over urban sprawl, which is viewed as a troubling phenomenon that increasingly threatens territorial balance. The rate at which natural and agricultural land is being consumed by urban development is accelerating, leading to a gradual and worrying reduction in natural and agricultural land. In the current context, it has become imperative to implement effective strategies to reduce the excessive consumption of bare land. Urban densification appears to be one of the most promising solutions for countering the phenomena of suburbanization and the degradation of natural soils. This perspective seeks to reduce the irrational use of natural and agricultural spaces while ensuring the conservation of resources for future generations, aligning with the principles of sustainable development. The results of this research show that urban densification, which corresponds to optimizing the use of space in urban areas, has the effect of reducing the mineralization of bare soil. This reduction is the result of the city building on itself rather than extensively. The research highlights the decisive impact of urban densification as an effective tool in the fight against urban sprawl. However, this approach to sustainable development is not sufficient on its own; it must be integrated into an overall policy framework for sustainable development, combining different mechanisms for action.